Guarantees in Banking Operations with Bank Customers - Vasile Dedu; Adrian Enciu (Theoretical and Applied Economics, 2009)
In a crediting relationship, one of the parties involved – namely the creditor – is exposed to certain risks which impose taking measures to guarantee a debt. If, at the due date, the debtor cannot pay his/her debts and meet the assumed liabilities, the creditor can execute the legally constituted guarantees, on a contract basis, thus covering the debt.There are also situations when the state, being directly interested in promoting trade and cooperation with other economies or simply out of the wish to ensure a competitive and safer business environment, gets involved in insurance and guarantee operations. In such situations, the state does not interve